Dilemmas and Optimization Paths of Villager Participation in the Practice of the Point-Based System for Rural Governance in City H - Xue, Shengjiang (Journal of Global Economy, Business and Finance, 2026)
The points-based system, as an important innovative tool for modernizing rural governance, plays a crucial role in stimulating villagers' participation and improving the effectiveness of grassroots governance. H City, a typical region characterized by multi-ethnic populations and uneven economic and social development, has integrated the points-based system into its rural governance practices. By leveraging points supermarkets, Party building integration, and digital empowerment, it has promoted villager participation and achieved initial success in improving the living environment, cultivating civilized rural customs, and promoting harmony. However, prominent problems remain, including insufficient role of villagers, limited participation channels, low awareness of rules, and weak incentive effectiveness. These problems stem from passive participation habits, unidirectional rule-making, insufficient publicity, and a simplistic incentive structure. This paper, based on participatory governance, incentive theory, and collaborative governance theory, and considering the regional and ethnic characteristics of H City, proposes optimization paths from four dimensions: transforming governance concepts, improving institutional mechanisms, strengthening the foundation for participation, and optimizing the points system. This provides empirical reference and theoretical support for improving the quality and efficiency of the points-based system in rural governance in multi-ethnic areas and activating villagers' intrinsic motivation for participation.